Assessment of bone healing ability of calcium phosphate cements loaded with platelet lysate in rat calvarial defects. (November 2016) - Babo, Pedro S; Carvalho, Pedro P; Santo, Vítor E; Faria, Susana; Gomes, Manuela E; Reis, Rui L
Injectable calcium phosphate cements have been used as a valid alternative to autologous bone grafts for bone augmentation with the additional advantage of enabling minimally invasive implantation procedures and for perfectly fitting the tissue defect. Nevertheless, they have low biodegradability and lack adequate biochemical signaling to promote bone healing and remodeling. In previous in vitro studies, we observed that the incorporation of platelet lysate directly into the cement paste or loaded in hyaluronic acid microspheres allowed to modulate the cement degradation and the in vitro expression of osteogenic markers in seeded human adipose derived stem cells. The present study aimed at investigating the possible effect of this system in new bone formation when implanted in calvarial bilateral defects in rats. Different formulations were assessed, namely plain calcium phosphate cements, calcium phosphate cements loaded with human platelet lysate, hybrid injectable formulations composed of the calcium phosphate cement incorporating hyaluronin acid non-loaded microparticles (20% hyaluronin acid) or with particles loaded with platelet lysate. The degradability and new bone regrowth were evaluated in terms of mineral volume in the defect, measured by micro-computed tomography and histomorphometric analysis upon 4, 8 and 12 weeks of implantation. We observed that the incorporation of hyaluronin acid microspheres induced an overly rapid cement degradation, impairing the osteoconductive properties of the cement composites. Moreover, the incorporation of platelet lysate induced higher bone healing than the materials without platelet lysate, up to four weeks after surgery. Nevertheless, this effect was not found to be significant when compared to the one observed in the sham-treated group.